An Improved Wearable Resonant Wireless Power Transfer System for Biomedical Capsule Endoscope - Basar, Md Rubel; Ahmad, Mohd Yazed; Cho, Jongman; Ibrahim, Fatimah (Institute of Electrical and Electronics Engineers, 2018)
Magnetic resonant-based wireless power transfer system (WPTS) is an efficient way to energize critical biomedical devices, such as wireless capsule endoscopes, where a direct wire connection is not practical. However, low power transfer efficiency (PTE) and poor received power stability (RPS) are usually the main bottlenecks of WPTS in this application. Thus, this paper proposes an efficient WPTS that tremendously improves the PTE and enriches the RPS. In order to improve the PTE, an optimum three-coil inductive link is adopted with a compact wearable power transmitting coil-I (PTC-I) and a 2-3D power receiving coil. As a result, the stability is improved with the new configuration of the power transmission coil-III (PTC-III) and power combining technique at the receiving side. To confirm the validity of the proposed design, proof-of-concept prototypes were implemented for an experimental test. Results obtained from the experimental test assured that the proposed PTC-I-based system achieved a PTE of more than 8% while transferring 758 mW of power with 68.7% RPS. The best overall RPS attained by the proposed PTC-III based system is 79.2%. This system achieved a PTE of 5.4% transferring at least 570 mW of power. In comparison, the performance of the proposed designs greatly outweighs the previous designs.